From awareness to action: the role of personal values and ethical stance in opposing slave labor in the fashion supply chain - Rodrigo Martins Baptista; Raquel Cymrot; Diógenes de Souza Bido; Ana Clara Kaneko Ebert; José Ricardo Baptista; Alcides Barrichello (Social Sciences and Humanities Open, 2025)
This study investigates the personal characteristics that influence young consumers' intention to avoid brands associated with harmful labor practices in their supply chains, aligning with the goals of SDG 8.7 on decent work and economic growth. Employing a quantitative methodology, Principal Component Analysis and Multiple Linear Regression were utilized to explore factors shaping ethical purchasing behavior. Key findings reveal that socio-environmental concerns and fashion orientation positively impact this intention, with the principal component “Orientation to Social Causes” emerging as the most significant factor. Conversely, low levels of responsible consumption negatively affect ethical purchasing intentions, highlighting an information gap that could be addressed through educational campaigns. In particular, the component labeled “Orientation toward Social Causes” emerged as the primary predictor. Conversely, lower levels of responsible consumption correspond with diminished ethical purchasing, exposing an informational gap that necessitates targeted educational interventions. Prior volunteer or community involvement is positively associated with rejecting brands that do not meet labor standards, whereas social class, age, and international experience show no significant effect. Managerial implications emphasize the need for ethical marketing strategies that combine fashion with sustainability, stressing the importance of aligning brand narratives with young consumers' moral aspirations and identities. Recommendations include enhancing consumer awareness, engaging influencers, and increasing supply chain transparency. Despite limitations related to sample generalizability and the inherent constraints of a cross-sectional design, this study contributes substantially to theoretical and practical advancements in ethical consumption. Ultimately, it provides a platform for future research using qualitative and comparative methods to enhance our understanding of purchasing decisions amidst labor injustice and to examine education and media roles in shaping responsible consumer behavior.